DEPEND study protocol: early detection of patients with pancreatic cancer – a pilot study to evaluate the utility of faecal elastase-1 and 13C-mixed triglyceride breath test as screening tools in high-risk individuals. Issue 2 (25th February 2022) - Afolabi, Paul Remi; McDonnell, Declan; Byrne, Christopher D; Wilding, Sam; Goss, Victoria; Walters, Jocelyn; Hamady, Zaed Z
Abstract : Introduction: Pancreatic cancer (PC) is the fifth leading cause of cancer-related death in the UK. The incidence of PC is increasing, with little or no improvement in overall survival and the best chance for long-term survival in patients with PC relies on early detection and surgical resection. In this study, we propose the use of a diagnostic algorithm that combines tests of pancreatic exocrine function (faecal elastase-1 (FE-1) test and the 13 C-mixed triglyceride ( 13 C-MTG) breath test) to identify patients with PC that urgently needs imaging studies. Methods and analysis: This prospective pilot (proof of concept) study will be carried out on 25 patients with resectable PC, 10 patients with chronic pancreatitis and 25 healthy volunteers. This study will construct a predictive algorithm for PC, using two tests of pancreatic exocrine function, FE-1 test and the 13 C-MTG breath test. Continuous flow isotope ratio mass spectrometry in the 13 C-MTG breath test will be used to analyse enriched 13 CO2 in exhaled breath samples. The additional predictive benefit of other potential biomarkers of PC will also be considered. Potential biomarkers of PC showing abilities to discriminate between patients with PC from healthy subjects or patients with chronic pancreatitis will be selected by metabolomic analysis. Ethics and dissemination: The study was approved by the North of Scotland Research and Ethics Committee on 1 October 2020 (reference: 20/NS/0105, favourable opinion granted). The results will be disseminated in presentations at academic national/international conferences and publication in peer-review journals.